Expression of Angiogenic Factors in Patients With Sporadic Small Bowel Angiodysplasia. Issue 10 (November 2015) - Holleran, Grainne; Hall, Barry; O'Regan, Myra; Smith, Sinead; McNamara, Deirdre
Abstract : Goals: To identify putative angiogenic factors associated with sporadic small bowel angiodysplasia (SBA). Background: SBAs account for 50% of obscure gastrointestinal bleeding and due to delays in diagnosis and ineffective treatments, are associated with high levels of morbidity and mortality. Treatment development is impeded by a limited knowledge of the pathophysiology behind SBA formation. Study: We identified patients with definite sporadic SBA, and fecal immunochemical–negative controls were recruited from our institution's colorectal cancer screening program. Serum levels of VEGF, endoglin, Angiopoietin-2 (Ang-2), PDGF, Angiopoietin-1 (Ang-1), and TNF-α were measured using commercially available enzyme-linked immunosorbent assay kits. On the basis of serum results, we measured gene expression of target angiogenic factors in small bowel biopsy samples from angiodysplasias and unaffected tissue by quantitative PCR assessment. Results: Serum samples were analyzed from 40 SBA patients and 40 controls. Median serum levels of Ang-2 were significantly higher in patients than controls with levels of Ang-1 and TNF-α significantly lower. There were no differences in serum levels of VEGF, endoglin, or PDGF. Gene expression levels of Ang-1, Ang-2, and their receptor Tie2 were all significantly higher in biopsies from areas of angiodysplasia compared with normal small bowel. Conclusions: This study, the first to explore the role of angiogenic factors in SBA, has identified a positive association between SBA and the Angiopoietin pathway, with increased serum and mucosal expression of Ang-2, which could potentially be used as a serum biomarker and future therapeutic target to improve outcome in affected patients.